Professionalism and associated factors among health professions education students: A primary mixed-methods study from Qatar - Dalal Hammoudi Halat; Banan Mukhalalati; Aaliah Aly; Mohammed Seed Ahmed; Alaa Daud; Ahmed Malki (PLoS ONE, 2026)
Background Professionalism, the judicious use of communication, knowledge, and values for benefits of individuals and communities, is a keystone in health education, and is demarcated by distinct tenets. Professionalism among health professions education students at Qatar University (QU) has not been previously explored. The current study aimed at assessment of professionalism and its tenets among students at the five QU Health Sector colleges, and exploring associated factors. Methods A mixed-methods convergent parallel design was used. For the quantitative phase, data were collected anonymously from students using the Pharmacy Professionalism Instrument (PPI), which assesses overall professionalism score, and scores of six tenets: Excellence, Respect, Altruism, Duty, Accountability, and Honor/Integrity. The qualitative phase involved focus groups exploring students’ perspectives on professionalism and opportunities for its fostering. Results A total of 536 survey responses were analyzed. The mean PPI score indicated fair levels of professionalism and Excellence, Altruism, Duty and Honor/Integrity tenets, while Accountability and Respect exhibited excellent levels. Scores statistically increased with study progress for overall professionalism, as well as Excellence and Respect tenets. Focus groups confirmed student views on tenets of Excellence, Respect, Altruism, Accountability, and Honor/Integrity. Yet, a slight discrepancy in the latter tenet emerged regarding necessity of reporting errors, with some students expressing concerns about potential consequences. Conclusion Favorable professionalism development across years of study and some excellent professionalism tenets were revealed among students. Amidst evolution in education and sociocultural norms, health education curricula should uphold cultivation of professionalism concepts, and establish an environment of recognition and nurturing of professionalism.